2020
DOI: 10.3390/w12123299
|View full text |Cite
|
Sign up to set email alerts
|

Hydroclimatic Extremes in the Limpopo River Basin, South Africa, under Changing Climate

Abstract: This research study evaluated the projected future climate and anticipated impacts on water-linked sectors on the transboundary Limpopo River Basin (LRB) with a focus on South Africa. Streamflow was simulated from two CORDEX-Africa regional climate models (RCMs) forced by the 5th phase of the Coupled Model Inter-Comparison Project (CMIP5) Global Climate Models (GCMs), namely, the CanESM2m and IPSL-CM5A-MR climate models. Three climate projection time intervals were considered spanning from 2006 to 2099 and del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…A study that used two CORDEX-Africa regional climate models (i.e., CanESM2m and IPSL-CM5A-MR) considered projected changes in precipitation in the Limpopo River basin [ 22 ]. It found that the basin is likely to experience reduced streamflow in the near and distant future, as well as frequent dry and wet conditions that can be interpreted as drought and flash floods, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A study that used two CORDEX-Africa regional climate models (i.e., CanESM2m and IPSL-CM5A-MR) considered projected changes in precipitation in the Limpopo River basin [ 22 ]. It found that the basin is likely to experience reduced streamflow in the near and distant future, as well as frequent dry and wet conditions that can be interpreted as drought and flash floods, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrological drought is associated with a reduction in the groundwater and/or surface-water resources, including river flows, reservoir storage and acquires [35], consequently affecting water supply for various purposes, including domestic, agriculture, power generation and recreation, among others. The SSI has been applied in various studies globally for the assessment of hydroclimatic extremes [23], characterization of anomalies in streamflow data [17,36], drought assessment [37], etc. While there has been no consensus on the exact methodology to use in the computation of the SSI, two approaches have been proposed in the literature by Modarres [36] and Vecente-Serrano et al [17].…”
Section: Methodsmentioning
confidence: 99%
“…These include drought characteristics over the Western Cape province [10], in the Free State and North West provinces [18], in Mpumalanga, Kwa-Zulu Natal, Free State, and North West provinces [19] and the Southern Africa [20]. Moreover, drought propagation using SPI and SSI was reported by Reference [21], as well as drought-risk assessment in the Eastern Cape province [22], hydroclimatic extremes in the Limpopo River Basin [23] and drought characteristics based on the SPI and EDI in the Free State province [24], among others.…”
Section: Introductionmentioning
confidence: 99%
“…The basin has a semi-arid climate, with wet summers and dry winters. The Mean Annual Precipitation (MAP) in the LTRB ranges from 300 to 700 mm/year with most of the rainfall occurring during the October to April period (Botai et al, 2020). Temperatures in the LTRB follow a distinct seasonal cycle with the coolest months occurring in winter (June-August), and hottest occurring in late summer (late November-early December).…”
Section: Study Areamentioning
confidence: 99%